Implementasi Kebijakan Pemberantasan Penyakit Demam Berdarah Dengue (DBD) Di Kecamatan Marpoyan Damai Kota Pekanbaru - Sri Ramadhani Yulia Putri; Nur Laila Meilani (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Dengue Hemorrhagic Fever (DHF) is a contagious disease that originates from the Aedes Aygpty mosquito and is caused by the Dengue virus. Dengue Hemorrhagic Fever (DHF) has long been known in Indonesia, where it can spread and become an epidemic, disrupting the social life of communities in a region. Marpoyan Damai District is one of the district with the highest incidence of Dengue Hemorrhagic Fever (DHF) in the city of Pekanbaru. The purpose of this study is to determine the Implementation of the Dengue Hemorrhagic Fever (DHF) eradication policy and to identify the factors that influence its implementation. This study uses a descriptive research method with a qualitative approach. The theoretical concept used is from Charles O. Jones` policy implementation model, which includes Organization, Interpretation, and Application/Implementation. The result of the study show that the implementation of the Dengue Hemorrhagic Fever (DHF) eradication policy in Marpoyan Damai District has not been fully effective, as seen from the low understanding of the community regarding mosquito breeding site eradication activities (PSN) and the inactivity of the Operational Work Group (Pokjanal) for the eradication of Dengue Hemorrhagic Fever (DHF) disease.